Modern coffee agroecosystems and their relationship with the conservation of butterflies in fragmented landscapes - Pérez-García, Oscar; Benjamin, Tamara J.; Tobar, Diego Enrique (Revista de Biología Tropical, 2018)
Land use change by the intensification of agriculture contributes to tropical forest fragmentation and biodiversity loss. In this sense, in comparison with traditional agroforestry systems (AFS), modern AFS are considered irrelevant for the conservation of biodiversity of tropical forest fragments. However, there is an increasing trend toward the establishment of different types of modern AFS. Owing to the sensitivity to environmental changes, we evaluated the biodiversity of butterflies in AFS with Coffea arabica and Erythrina poeppigiana (CP), and intermixed with Musa spp. (CPM) or Cordia alliodora (the only native species of AFS) (CPL), as well as premontane very humid forest fragments in the Volcánica Central-Talamanca Biological Corridor, Costa Rica. In six representative sites of each system we set up three parallel 80 m line-transects, separated by a distance of 25 m. Each coffee farm and forest fragment (FR) was surveyed during 1.5 hours to record butterflies. All sites were sampled once a month from May to July 2007. We obtained 4.5 hours of sampling/site, and 27 hours of sampling/habitat. Both CP and CPM together had a butterflies’ species composition which differed from CPL and FR. The indicator species of both CP and CPM together were Hermeuptychia hermes and Anartia jatrophae which are typical of open areas. CPL resulted with the species of secondary forests Heliconius erato petiverana and Pareuptychia ocirrhoe as indicators. In contrast, FR resulted with several indicator species typical of closed canopy forests such as Pierella helvina incanescens, Caligo eurilochus, and Morpho peleides limpida. Moreover, the richness of species was similar among coffee AFS. Furthermore, the richness of species of each coffee AFS was lower in comparison with FR. However, among coffee AFS, CPL harbored higher diversity (Exp(H’)) of forest butterflies than CP. Also, CPM was higher in abundance of frugivorous butterflies in relation with CP and CPL. In fragmented forests, coffee farms with exotic shade species combined at least with a native tree or fruit species, can be a better habitat for forest butterflies than those dominated by an exotic monospecific shade.